Analysis of the Impact of Gross Split Production Sharing Contracts in the Upstream Oil and Gas Sector on State Revenue - Rizal, Mohamad Nor; Murwani, Sri (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — Since 2017, Oil and Gas Cooperation Contract Contractors (KKKS) have had the option to use Gross Split (GS) Production Sharing Contracts (PSC) to manage oil and gas (migas) work areas (WK) as an alternative to the Cost Recovery (CR) PSC, which has been in place since the 1960s. However, despite its implementation since 2017, no research has specifically examined the impact of GS PSCs on state revenue. Most studies have instead focused on their effect on KKKS profitability. Research Objectives — This study aims to provide empirical evidence on the impact of GS PSC implementation in managing oil and gas WKs, particularly in relation to state revenue. Research Methods — The study employs a difference test and an impact test. The difference test utilizes data from six relatively similar WKs in 2018, while the impact test is conducted using data from 35 WKs over the period 2018–2022. Empirical Results — The findings indicate that state revenue from a WK decreases after transitioning to the gross split scheme. Additionally, gross split has a significant negative impact on state revenue. Other variables significantly and negatively affecting state revenue include operating costs, lifting, and selling prices. Conversely, contractor profit has a significant positive effect on state revenue. Implications — The results suggest that adopting gross split PSCs and/or increasing operating costs will reduce state revenue in the current year. Conversely, higher lifting volumes, selling prices, and contractor profits contribute to increased state revenue in the same period.